The Effects of Interest Rate and Exchange Rate on Stock Returns - Boo, Hooi Laing (2010)
For more than 30 years, the relationship between exchange rates, interest rate and stock price has drawn attention of economists, because they both play crucial roles in influencing the development of a country's economy. Many studies have been conducted both theoretically and empirically. The main objective of this study is to examine whether exchange rate and interest rate influence shareholder wealth. The sample period for this study is from Jan 1, 1990 to Dec 31, 2009, and the monthly data of company return, market return, Malaysia real effective exchange rate per US Dollar, and Kuala Lumpur base lending rate were gathered from DataStream. This study attempts to investigate the influence of exchange rate and interest rate to shareholder wealth within the investigated period controlling for the time periods D4CC and D4AFC. Thus I divided the covering period to three subperiods. First is from January 1, 1990 to Jun 31, 1997 and from August 1, 2005 to November 30, 2009. Second, during Asian financial crisis, that is from July 1, 1997 to August 31, 1998. Third, during capital control period, which is from September 1, 1998 to July 31, 2005. The models applied in this study includes descriptive statistics, comparisons between different time periods, correlation test and multiple regression. The results show that, first, exchange rate and interest rate are significant in the multiple regression equation. The relationships between the exchange rate and the stock market return are in line with expectation because the result indicated that the lower is the value of Ringgit Malaysia, the higher is the stock return. From the findings of this study, the effects of the exchange rate, interest rate, and market return to shareholder wealth are significant.